The progressive mystery tracing the elusive Spirit in Scripture & tradition - Habets, Myk 1971- (Bellingham, WA Lexham Press, 2019)
Myk Habets carefully explores the progressively revealed identity and mission of the Holy Spirit as revealed throughout Holy Scripture and then interpreted by the Church. As a work of biblical theology, the focus of Parts 1 & 2 is on how the identity of the Spirit has been revealed, understood, and interpreted throughout the sweep of Holy Scripture. As a contribution to historical theology, the focus on Parts 3 & 4 is on the ways in which the orthodox understanding of the mission of the Holy Spirit has developed. This study offers graduate students the ideal entrée into the study of pneumatology as it opens the windows on Scripture and Tradition in ways which allow others to see what is going on. Taking its place among other introductions to pneumatology, this study is a readable and reliable guide to what is often considered the elusive Holy Spirit of God
Includes bibliographical references (pages 185-203) and indexes
Keywords: Holy Spirit; Holy Spirit -- Biblical teaching; Holy Spirit ; Biblical teaching